2020
DOI: 10.1155/2020/5417598
|View full text |Cite
|
Sign up to set email alerts
|

A Circulating Long Noncoding RNA Panel Serves as a Diagnostic Marker for Hepatocellular Carcinoma

Abstract: Background. Circulating long noncoding RNAs (lncRNAs) have been demonstrated to serve as diagnostic biomarkers for various cancers. We aimed to elucidate the diagnostic efficacy of eight serum lncRNAs HULC, MALAT1, Linc00152, PTENP1, PTTG3P, SPRY4-IT1, UBE2CP3, and UCA1 and their combinations for the diagnosis of hepatocellular carcinoma (HCC). Methods. A total of 129 patients with HCC, 49 patients with liver cirrhosis, 27 patients with chronic hepatitis B, and 93 healthy controls were enrolled in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 40 publications
(65 reference statements)
2
61
1
Order By: Relevance
“…Further research showed that circulating HULC in HCC patients could be used as a diagnostic marker, being highly up-regulated in patients with HCC compared to healthy individuals [ 39 , 40 , 41 ], with the area under the curve (AUC) of the receiver operator characteristic (ROC) curve around 0.80. Several studies; however, did not find up-regulation of HULC in HCC samples set [ 16 , 42 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 4 more Smart Citations
“…Further research showed that circulating HULC in HCC patients could be used as a diagnostic marker, being highly up-regulated in patients with HCC compared to healthy individuals [ 39 , 40 , 41 ], with the area under the curve (AUC) of the receiver operator characteristic (ROC) curve around 0.80. Several studies; however, did not find up-regulation of HULC in HCC samples set [ 16 , 42 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…It was hypomethylated in tumor tissues and human HCC cell lines [ 68 ] and during hepatocarcinogenesis [ 69 ]. In the blood, the expression level of LINC00152 increased from normal healthy control to chronic hepatitis B, liver cirrhosis, being highest in HCC [ 41 , 42 ]. Among other lncRNAs including HULC, LINC00152 was found to be the best diagnostic lncRNA with high AUC and sensitivity/specificity values [ 41 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 3 more Smart Citations